Dogmatics After Babel: Beyond the Theologies of Word and Culture, by Rubén Rosario Rodriguez - Glass, Stetson (Pneuma, 2020)
"Dogmatics After Babel: Beyond the Theologies of Word and Culture, by Rubén Rosario Rodriguez" published on 16 Apr 2020 by Brill.